Dynamics of capital structure determinants: empirical evidence from GCC countries - Shoaib Khan; Tahir Akhtar; Ameen Qasem (Future Business Journal)
Abstract The study empirically examines the factors affecting the financing decisions of non-financial listed companies in Gulf Cooperation Council (GCC) countries. Using static and dynamic two-step generalized method of moments techniques, it analyzes unbalanced panel data from 364 non-financial companies across six GCC countries from 2011 to 2021. The findings partially support optimal capital structure theories, highlighting significant internal factors such as profitability, market-to-book ratio, firm size, earnings volatility, and growth opportunities that influence financing decisions. While no single theory fully explains the financing choices, the association of internal factors with book and market leverage is consistent. The study provides robust and generalizable results, aiding financial institutions and policymakers in formulating pro-development policies and regulations. This research facilitates better coordination between corporate managers and financial institutions, supporting the region’s economic transition. It is the first study to use extensive data from GCC non-financial firms to investigate financing decisions, offering valuable insights for investors and a basis for further analysis of capital structure choices in the region and beyond.